PENGARUH LITERASI KEUANGAN, TEMAN SEBAYA DAN DISONANSI KOGNITIF TERHADAP PERILAKU KONSUMTIF: (Survey pada Siswa SMA Negeri se-Kota Tasikmalaya) - Barokah, Fajriyatul; Hermawan, Yoni; Srigustini, Astri (Transpublika Publisher, 2023)
The problem addressed in this study is the excessive consumption of non-essential needs among high school students in Tasikmalaya, coupled with their inability to establish a priority scale for their consumption patterns. This research employs a quantitative survey method with an explanatory survey design. The study's target population includes all public high school students in Tasikmalaya City, specifically those in class XI. The sampling technique utilized in this study is probability sampling, employing proportionate random sampling, resulting in a sample size of 367 students. Data collection is carried out through the use of questionnaires, while data analysis is performed using the SPSS 25.0 for Windows program. The results indicate the following: 1) There exists a significant correlation between financial literacy and consumptive behavior, with a significance value of 0.045. 2) Peers exert a notable influence on consumptive behavior, as evidenced by a significance value of 0.029. 3) Cognitive dissonance also significantly impacts consumptive behavior, with a significance value of 0.029. 4) The combined effect of financial literacy, peers, and cognitive dissonance on consumptive behavior is significant, demonstrated by a significance value of 0.000.